MANAJEMEN STRATEGIS PENINGKATAN MUTU DOSEN DI PERGURUAN TINGGI SWASTA - Asep Tutun Usman; Iim Wasliman; Ujang Nurjaman; Faiz Karim Fatkhullah (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
This study aims to describe and analyze the strategic management of improving the quality of lecturers in private universities (case studies of Umtas Tasikmalaya and IPI Garut). The research procedure used is a qualitative approach with a case study design. Data collection techniques were carried out by (1) Observation, (2) Interview and (3) Documentation. Data collection techniques used are observation and interviews. While the data analysis techniques used through several stages, including data collection, data presentation and drawing conclusions. The impact of strategic management on improving the quality of lecturers in private universities is sufficient to improve the quality of education, research quality, and community service quality. This can be seen from several lecturers who actively participate in the Tri Dharma College activities. So, this research was conducted in order to improve explaining that the strategic management of improving the quality of lecturers has been realized in accordance with the principles of strategic management theory and quality theory, so that the improvement of the quality of lecturers is realized.